Variables asociadas a severidad del cáncer gástrico en pacientes atendidos en oncología del Hospital Regional de Loreto Iquitos 2021 al 2022 - Pilco Vela, Nora Brisol (2025)
The objective of the research was to determine the variables associated with the severity of gastric cancer in patients treated in Oncology at the Regional Hospital of Loreto, Iquitos 2021 - 2022. The method used was quantitative with a non-experimental, descriptive, correlational, retrospective and cross sectional design. For the study, a sample of 78 medical records of patients diagnosed with gastric cancer at the Loreto Regional Hospital from 2021 to 2022 was used. The technique was the documentary review and the instruments were the Data Sheet of patients with gastric cancer and the Registration Form for the identification of the stage of severity of gastric cancer. For the analysis of information, the statistical software SPSS version 24.0 was used and for the correlation of data the statistical test chi square (x²) was used. The results were: 53.8% (42) were between 30 and 59 years old, 52.6% (41) were male, 67.9% (53) had other occupations, 48.7% (38) had anemia and 93.6% (73) have been diagnosed in the last year. Likewise, on the stage of severity of gastric cancer, 32.1% (25) were in stage 3, 26.9% (21) were in stage 1, 24.4% (19) in stage 4, 9.0% (7) in stage 2 and the remaining 7.7% (6) in stage 0. In conclusion, an association was found with: Comorbidity p = 0.037 and Time of diagnosis p = 0.023.